The Effectiveness of the Reflective Learning Strategy Using the Blackboard System and WhatsApp application on Academic Achievement and the trend towards the use of the Internet in the education among Female Students of the Department of Home Economics - Zahid, Manal Abdullah (Arab Journal for Sciences and Research Publishing, 2016)
The use of technology and communication methods in teaching is inevitable given the rapid spread of various technological applications and the use of the students for them have continuously, while effective ways traditional strategies in teaching fell, and in this context, targeting current research measure the effectiveness of Reflective Learning strategy using Blackboard system and What's up application on Academic achievement and the trend towards the use of the Internet in the education of students' Home Economics Department, Faculty of Education, Prince Sattam bin Abdul-Aziz University, where the sample reached (89) students were selected (44) of them - at random - to represent  the experimental group which studied the courses of teaching methods (2) according to the Reflective Learning strategy and accounted for (45) student control group which studied the traditional way (interactive lecture), and applied to the study of achievement test with the courses tools and the scale toward the direction based education on the Internet, after the statistical treatment of the results of the study researcher found to effectively reflective Learning strategy using Blackboard system and What's up application on achievement test courses teaching methods results (2) for the benefit of the experimental group compared to the traditional teaching using interactive lecture for the control group, also found the presence of elevated denote the trend towards based on internet education for the experimental group versus the control group and that based on the application of the scale (the trend toward education based on internet for good results), the study recommended to the importance of the application of teaching strategies that rely on internet applications and electronic communication programs as well as student-centered strategies.
Keywords: Flipped education; Blackboard system; WhatsApp application; trend towards Internet-based education; Department of Home Economics; academic achievement